Helicobacter pylori infection and polycystic ovary syndrome in adolescent and young adult patients. Issue 12 (19th September 2016) - Tokmak, Aytekin; Doğan, Zeynal; Sarıkaya, Esma; Timur, Hakan; Kekilli, Murat
Abstract: Aim: Polycystic ovary syndrome (PCOS) is the most common cause of infertility among women of reproductive age. Chronic systemic inflammation has been considered to play a role in the development of PCOS. Helicobacter pylori has been shown to lead to both local gastric and chronic systemic inflammation. In the light of this, the aim of the present study was to investigate a possible link between H. pylori and PCOS. Methods: A total of 167 nullipar and single adolescent and young adults (AYA) were recruited for the study: 86 (51.5%) had PCOS and 81 (48.5%) were age‐matched controls. The average age was 18.57 ± 2.40 (range, 14–24 years). The recent Amsterdam European Society of Human Reproduction and Embryology/American Society for Reproductive Medicine (ESHRE/ASRM) guidelines including all three of the Rotterdam criteria were used to diagnose PCOS, and enzyme‐linked immunosorbent assay kit was used to measure H. pylori IgG. Results: There was no significant association between the PCOS and non‐PCOS groups with regard to the presence of H. pylori IgG ( P = 0.924), white blood count or C‐reactive protein ( P = 0.064; P = 0.383, respectively). Conclusion: The prevalence of H. pylori was not different with regard to PCOS status in AYA. More studies are needed to investigate a possible link between PCOS and H. pylori .